Anger, gratitude, and the Enlightenment writer - Coleman, Patrick (Oxford : Oxford University Press, 2011)
On the one hand, anger and gratitude are crucial in appreciating what one owes to oneself or others; on the other, they disturb one's internal balance and reinforce one's dependence upon others. This book explores the tension between these two attitudes in the work of French Enlightenment writers such as Rousseau, Diderot, and Marivaux.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 16, 2010).
Keywords: French literature -- 18th century -- History and criticism; Anger in literature; Gratitude in literature